A Metallic Ion‐Induced Self‐Assembly Enabling Nanowire‐Based Aerogels. Issue 44 (24th September 2021) - Shang, Qi‐Guo; Wang, Kang; Li, Lin‐Ge; He, Zhen; Jiang, Hui‐Jun; Zhu, Jian‐Hua; Liu, Jian‐Wei
Abstract: The controlled assembly of nanowires is one of the key challenges in the development of a range of functional 3D aerogels with unique physicochemical properties for practical applications. However, the deep understanding of the dynamic assemble process for fabricating nanowire aerogels remains elusive. Herein, a facile strategy is presented for the metallic ion‐induced assembly of nanowires into macroscopic aerogels via a solution‐based process. This method enables the interconnecting between polymer‐decorated nanowires via metallic coordination, resulting in plenty of nanowire bundles with the same orientation. Besides, the coordinated binding strength of nanowires with different metallic ions is also discussed. The assembly mechanism that the metallic ions induced dynamic behavior of nanowires is revealed via molecular dynamics theoretical evaluation. These findings benefit for constructing nanowire‐based aerogels with unique structural features and multi‐function, which pave new opportunities for other material systems. Abstract : Herein, a facile strategy is presented for the metallic ion‐induced assembly of nanowires into 3D aerogels via a hydrothermal process. The coordinated binding strength of nanowires with different metallic ions as well as the metallic ions induced dynamic behavior of nanowires are revealed via molecular dynamics theoretical evaluation.